Implementation Cooperative Learning Type STAD Assisted Edmodo in Improving Students' Critical Thinking Skills - Muhamad Epi Rusdin; Widodo Widodo; Guntur Maruto (Universitas Ahmad Dahlan, 2020)
The STAD cooperative learning model can support active, independent and responsible learning for students. The application of this model is expected to improve students' critical thinking skills. The purpose of this study was to determine the improvement of students' critical thinking skills using Edmodo-assisted learning models. Edmodo was modified to become a teacher tool to expand learning at home. This research is an experimental study using a pretest-posttest control group design involving 39 students of class VIII MTs At-Taqwa Beru, Sikka, East Nusa Tenggara. Based on the results of the study it was found that the Edmodo-assisted STAD type cooperative learning model can improve students' critical thinking skills.